Hubungan Antara Diabetes Melitus Dengan Penyakit Arteri Perifer Di Posyandu Lansia Kelurahan Pucangan - Wening Afta Fitria, Laksmi, Isnaini Herawati, SST.FT., M.Sc (2017)
ABSTRACT Background: Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia due to abnormalities in insulin secretion, insulin action, or both. DM can cause some complications one of them is atherosclerosis. PAP is the biggest cause of atherosclerosis. Atherosclerosis of DM will be seen from DM due to endothelial function, DM against platelets, and its effect on coagulation and rheological. PAP prevalence in Indonesia is 9.7% (Fowkes, 2006). DM can increase the risk of incidence of symptomatic and asymptomatic PAP by 1.5-4 fold (Rangkuti, 2008). According Thiruvoipati (2015), the prevalence of PAP screening using the ABI (Ankle Brachial Index) in diabetic patients aged> 50 years by 29%. Purpose: To determine the correlation between DM with PAP. Methods: This research is an observational research with cross sectional method. Technical sampling using quota sampling of 107 respondents. Primary data was taken from the examination of blood sugar levels and Peripheral Artery Disease using a sphygmomanometer and stethoscope. Status of Diabetes Melltius reinforced with secondary data from medical records of respondents. Status of Peripheral Arterial Disease measured by ABI. Carried out after the break 5-30 minutes. Statistical testing using Fisher Exact test. Result: Respondents were DM but normal ABI as many as five people (7.7%), diabetes mellitus with normal ABI is not as much as 6 (3.3%). While respondents Non-DM with normal ABI as many as 70 people (67.3%), Non DM but not normal ABI as many as 26 people (28.7%). This data was tested by Fisher's Exact values obtained p = 0.082, which means there is no correlation between Diabetes Mellitus with Peripheral Arterial Disease. Conclusion: There is no correlation between Diabetes Mellitus with Peripheral Arterial Disease. Keywords: Diabetes Mellitus, Peripheral Arterial Disease, Ankle Brachial Index